Association between haploidentical hematopoietic stem cell transplantation combined with an umbilical cord blood unit and graft-versus-host disease in pediatric patients with acquired severe aplastic anemia. (October 2022) - Yao, Di; Tian, Yuanyuan; Li, Jie; Li, Bohan; Lu, Jun; Ling, Jing; Zheng, Defei; Yao, Yanhua; Xiao, Peifang; Meng, Lijun; Hu, Shaoyan
Background: Haploidentical hematopoietic stem cell transplantation (haplo-HSCT) based on granulocyte colony-stimulating factor plus anti-thymocyte regimens ('Beijing Protocol') provides a salvage treatment for patients of acquired severe aplastic anemia (SAA) in China. However, graft- versus -host disease (GVHD) is a major impediment of haplo-HSCT due to human leukocyte antigen disparity. Recently, haplo-HSCT combined with umbilical cord blood (UCB) (haplo-cord HSCT) is performed in clinical trials to potentially reduce the risk of severe GVHD. Nevertheless, studies comparing GVHD in pediatric patients receiving haplo and haplo-cord HSCT for SAA are limited. Objective: The objective of this study was to investigate the impact of UCB co-infusion on GVHD in pediatric patients receiving haplo-HSCT for SAA. Design: We conducted a retrospective study of 91 consecutive SAA children undergoing haploidentical transplantation based on the 'Beijing Protocol' with or without co-infusion of UCB in our center. Methods: All patients received uniform non-myeloablative conditioning and GVHD prophylaxis. We compared baseline characteristics and transplant outcomes between the haplo ( n  = 35) and haplo-cord ( n  = 56) recipients. Results: All 91 patients achieved hematopoietic recovery from haploidentical donors, with a higher incidence of peri-engraftment syndrome observed with the haplo-cord group as compared with the haplo group (75.0% versus 48.6%, p  = 0.029). Notably, the haplo-cord group showed a lower incidence of II–IV acute GVHD (aGVHD) than the haplo group (16.1% versus 42.9%, p  = 0.002). Observed incidences of chronic GVHD (cGVHD) and moderate to severe cGVHD in the haplo-cord group were also lower than that in the haplo group (25.6% versus 51.3%, p  = 0.019; 16.2% versus 41.3%, p  = 0.016, respectively). Haplo-cord HSCT was identified as the only factor associated with a lower incidence of II–IV aGVHD and cGVHD in multivariate analysis. However, no differences were observed between the two groups for infections and survival outcomes. Conclusion: Our data indicated that co-infusion of UCB in 'Beijing Protocol'-based haplo-HSCT may be effective for reducing the risk of severe GVHD in SAA children.